Maintenance of air conditioning in Hotel Perdana Kota Bharu building / Ahmad Muzakkir Ahmad Fauzi - Ahmad Fauzi, Ahmad Muzakkir (2016)
Generally, this report is about the system of air conditioning system that has been used and maintenance of air conditioning system in the Hotel Perdana building. This hotel are used two type of air conditioning system which is centralized air conditioning system with water-cooled system and split unit air conditioning system. Basically, this system contains of three chillers, six Chilled Water Pump (CHWP), six Condensate Water Pump (CWP) and three unit cooling towers that have nine cells of cooling fan located at roof level 4. This report also describes the type of air conditioning system which is used in building with specification and details for every type of air conditioning system. Then, the process of managing and maintenance of air conditioning system in building also as main report which is most important part because to achieve the comfortable of guest hotel and reduce complaint about the problems of the air conditioner in room or hall in building. Lastly, this report also have discuss the several problems and recommendation to manage and maintenance of air conditioning problems that usually occur in this building.